Identification of Single Nucleotide Polymorphism in TaSBEIII and Development of KASP Marker Associated With Grain Weight in Wheat - Irshad, Ahsan; Guo, Huijun; Ur Rehman, Shoaib; Wang, Xueqing; Gu, Jiayu; Xiong, Hongchun; Xie, Yongdun; Zhao, Linshu; Zhao, Shirong; Wang, Chaojie; Liu, Luxiang (Frontiers in Genetics, 2021)
Manipulation of genes involved in starch synthesis could significantly affect wheat grain weight and yield. The starch-branching enzyme (SBE) catalyzes the formation of branch points by cleaving the -1,4 linkage in polyglucans and reattaching the chain via an - 1,6 linkage. Three types of SBE isoforms (SBEI, SBEII, and SBEIII) exist in higher plants, with the number of SBE isoforms being species-specific. In this study, the coding sequence of the wheat TaSBEIII gene was amplified. After the multiple sequence alignment of TaSBEIII genome from 20 accessions in a wheat diversity panel, one SNPs was observed in TaSBEIII-A which formed allelic marker allele-T. Based on this SNP at 294 bp (C/T), a KASP molecular marker was developed to distinguish allelic variation among the wheat genotypes for thousand grain weight (TGW). The results were validated using 262 accessions of mini core collection (MCC) from China, 153 from Pakistan, 53 from CIMMYT, 17 diploid and 18 tetraploid genotypes. Association analysis between TaSBEIII-A allelic variation and agronomic traits found that TaSBEIII-A was associated with TGW in Chinese micro core collection (MCC). The accessions possessing Allele-T had higher TGW than those possessing Allele-C, thus Allele-T was a favorable allelic variation. By analyzing the frequency of favorable allelic variation Allele-T in MCC, it increased from pre-1950 (25%) to 1960s (45%) and increased continuously from 1960 to 1990 (80%). The results suggested that the KASP markers can be utilized in grain weight improvement which ultimately improves wheat yield by marker-assisted selection in wheat breeding. The favorable allelic variation allele-T should be valuable in enhancing grain yield by improving the source and sink simultaneously. Furthermore, the newly developed KASP marker validated in different genetic backgrounds could be integrated into a breeding kit for screening high TGW wheat.